2022
DOI: 10.1007/s00227-022-04032-z
|View full text |Cite
|
Sign up to set email alerts
|

Linking the dynamic organization of the ovary with spawning dynamics in pelagic fishes

Abstract: The link between the dynamic organization of the ovary and spawning dynamics was investigated in pelagic fishes with indeterminate fecundity. Αn array of laboratory methods and statistical approaches was applied to samples of gonadal material from three commercial NE Atlantic fish species: the sardine, Sardina pilchardus, the horse mackerel, Trachurus trachurus, and the mackerel, Scomber scombrus. Methods included the application of clustering analysis algorithms in histological specimens and the application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
(84 reference statements)
2
1
0
Order By: Relevance
“…One should, however, expect that the overall rate of vitellogenin uptake ( ∆ VDW overall ) would fall if a persistently high T is introduced prior to spawning due to the foreseen reduction in 17β‐estradiol in several species (Alix et al, 2020). Anyhow, our formulations confirmed that the teleost ovulatory cycle is highly complex in nature (Charitonidou et al, 2022); in cod probably at least two oocyte cohorts co‐develop. The further process of validation of ∆ VDW overall showed, however, clear examples of underestimates for larger individuals, suggesting that a much bigger share of the vitellogenic raw material is stored in muscle and liver in larger than smaller females (Jansen et al, 2021; Kjesbu et al, 1991).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…One should, however, expect that the overall rate of vitellogenin uptake ( ∆ VDW overall ) would fall if a persistently high T is introduced prior to spawning due to the foreseen reduction in 17β‐estradiol in several species (Alix et al, 2020). Anyhow, our formulations confirmed that the teleost ovulatory cycle is highly complex in nature (Charitonidou et al, 2022); in cod probably at least two oocyte cohorts co‐develop. The further process of validation of ∆ VDW overall showed, however, clear examples of underestimates for larger individuals, suggesting that a much bigger share of the vitellogenic raw material is stored in muscle and liver in larger than smaller females (Jansen et al, 2021; Kjesbu et al, 1991).…”
Section: Discussionsupporting
confidence: 81%
“…One should, however, expect that the overall rate of vitellogenin uptake Cod spawning grounds displacement (∆VDW overall ) would fall if a persistently high T is introduced prior to spawning due to the foreseen reduction in 17β-estradiol in several species (Alix et al, 2020). Anyhow, our formulations confirmed that the teleost ovulatory cycle is highly complex in nature (Charitonidou et al, 2022); in cod probably at least two oocyte cohorts co-develop.…”
Section: Discussionsupporting
confidence: 57%
“…However, environmental conditions such as temperature and food availability and parameters such as fish condition can act synergistically and affect reproductive characteristics (oocyte size, oocyte recruitment, spawning frequency, batch fecundity, duration of spawning period, etc. ), thus influencing a fish population's reproductive outcomes [18,34,36,[39][40][41][42][43]. Knowledge of ovarian dynamics and how they are influenced by environmental factors is very important, not only for applying egg production methods for fisheries stock assessments and management [44,45] but also for understanding and predicting impacts of climate change.…”
Section: Discussionmentioning
confidence: 99%